2022
DOI: 10.1021/acs.jpcb.2c03970
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume Model for Transport in Flexible Kerogen of Source Rock’s Organic Matter

Abstract: We build a model of transport of adsorbed fluid within the microporous network of kerogen’s porosity, especially accounting for the adsorption-induced swelling exhibited by flexible kerogen structures. This model, based on Fujita–Kishimoto free volume theory that was historically developed for swellable polymers, is built over extensive results for the self-diffusion coefficients obtained by molecular dynamics calculations for a representative molecular model of kerogen designed to study the importance of flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…We indeed observe a linear evolution (increase) of D s with φ f in all directions. This correlation between diffusion and free volume was also observed in former works , where adsorption induced swelling was significant enough to compensate for the fluid steric hindrance.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We indeed observe a linear evolution (increase) of D s with φ f in all directions. This correlation between diffusion and free volume was also observed in former works , where adsorption induced swelling was significant enough to compensate for the fluid steric hindrance.…”
Section: Resultssupporting
confidence: 84%
“…They have observed significant differences between the two matrices, showing that immature kerogen can swell up to a 20% increase in volume while the swelling of the overmature kerogen in the same conditions remains far below 1%. The large swelling experienced by the immature kerogen was subsequently shown to lead to an increase in diffusion coefficient with increasing loading at constant reservoir (P,T) conditions, 19,20 which is the opposite behavior to the commonly observed one for rigid hosts. More recently, a few studies have been reported in which adsorption-induced deformations in kerogen are accounted for via an hybrid method alternating GCMC cycles and short MD simulations in the isothermal−isobaric (NPT) ensemble.…”
Section: ■ Introductionmentioning
confidence: 86%
“…It is also shown that, at constant volume, the effects of the internal motions of the kerogen matrix coupled to the dynamics of the fluid enhance the diffusion and that this enhancement is more important at low fluid loading because pore size fluctuations have a more dramatic impact on the pore connectivity than at high loading where the pore network is always well connected. Following on this work, Ariskina et al highlighted that kerogen flexibility do not promote significant collective effects on the diffusion. Again, as in the rigid case, the collective- and the self-diffusion coefficients are approximately equal and the latter can be used to predict the transport properties.…”
Section: Fluid Thermodynamics and Transport In Kerogenmentioning
confidence: 79%
“…Lines are a guide for the eyes. (c) Self-diffusion coefficient for methane adsorbed in a QMD model of immature type I kerogen, as a function of the fluid loading in milligram of fluid per gram of matrix (reproduced with permission from ref . Copyright 2022 American Chemical Society).…”
Section: Fluid Thermodynamics and Transport In Kerogenmentioning
confidence: 99%
“…Throughout the simulations, atoms belonging to inorganic minerals and kerogen were treated as solid, suggesting that the possible swelling behaviors of kerogen when exposed to gas molecules were not taken into account. 38 2.2. Option of Force Field.…”
Section: Simulation Methodsmentioning
confidence: 99%